Photochemistry of HCl in rare gas matrices - Godders, K.; Schwentner, N. (Физика низких температур, 1996)
НС1 is dissociated by excitation to the purely repulsive A¹ Π state and the dissociation fragments are probed via the fluorescence from charge transfer states with the rare gas atom using tunable synchrotron radiation from BESSY (Berlin). The quantum efficiency for the dissociation of HC1 monomers in Xe matrices yields a matrix induced barrier of 1.4 eV and a linear increase with excess energy of the H atoms, which agrees with MD simulations. Dissociation of HC1 dimers leads to Cl₂ and H₂ formation by two different reaction mechanisms. In the low energy part (1.9 eV < £|yn < 4.4 eV), MD simulations suggest a reaction via multidimensional energy surfaces with a quantum efficiency below 1 %, which is confirmed by our experiments. In the higher energy part (Ekin > 4.4 eV) an impact mechanism is dominant, where the H fragment kicks the H atom off a nearby HC1 molecule. Photoinduced and thermal mobilities of H atoms in Xe and Ar matrices were measured. A pathlength for photomobilized H atoms of 19 A at a kinetic energy of 2.0 eV was estimated from the recombination efficiency of H and Cl atoms by thermal activation. In Ar matrices a H atom pathlength of (21 ± 2) A at = 2.5 eV was measured from the capture efficiency of codoped Xe traps. From theH loss at 44 К in Xe matrices a thermal diffusion constant of (7-2 ± 1.5) -10-¹³ cm²/s for H in Xe was determined.